2021
DOI: 10.1038/s41598-021-90159-w
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial working memory dysfunction from tapping span test as a diagnostic tool for patients with mild posterior cortical atrophy

Abstract: Posterior cortical atrophy is a rare degenerative condition with prominent visuospatial dysfunction which commonly occurs between ages 50 and 65. A diagnosis of mild posterior cortical atrophy sometimes challenging and can be delayed because there are currently no established neuropsychological examination methods that can easily be used in clinical settings. In this study, we examined whether the tapping span test is a potential diagnostic tool for posterior cortical atrophy and what impairment the tapping sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Our patient’s Digit Span Forward and Backward subtest scores were five and three spans, but her Tapping Span Forward and Backward subtest scores were only two and zero spans, respectively, suggesting a substantial difference between the Digit Span and Tapping Span subtests, which is a hallmark of dorsal simultanagnosia in individuals with PCA (Funayama et al, 2021).…”
Section: Resultsmentioning
confidence: 75%
“…Our patient’s Digit Span Forward and Backward subtest scores were five and three spans, but her Tapping Span Forward and Backward subtest scores were only two and zero spans, respectively, suggesting a substantial difference between the Digit Span and Tapping Span subtests, which is a hallmark of dorsal simultanagnosia in individuals with PCA (Funayama et al, 2021).…”
Section: Resultsmentioning
confidence: 75%
“…The CAT is a validated, reliable, and Struggling to grasp an object in front of him/her with each hand Perceiving everything at the same distance Seeing everything as if it is at the same distance, appearing flat like a painting on the wall standardized test that has been widely used to assess attentional function in Japan for more than a decade. We assessed these two types of working memory because visuospatial working memory dysfunction, as well as the difference between the two span tests, is closely related to the severity of dorsal simultanagnosia (Funayama et al, 2015(Funayama et al, , 2021, which was observed in patient 3.…”
Section: Clinical Assessment For Attentionmentioning
confidence: 99%
“…The CAT is a validated, reliable, and standardized test that has been widely used to assess attentional function in Japan for more than a decade. We assessed these two types of working memory because visuospatial working memory dysfunction, as well as the difference between the two span tests, is closely related to the severity of dorsal simultanagnosia (Funayama et al, 2015, 2021), which was observed in patient 3.…”
Section: Assessmentsmentioning
confidence: 99%
“…Visuospatial function was evaluated using the Japanese version of the Trail Making Test A (TMT-A) [12]. The span tests, i.e., Tapping Span Forward and Digit Span Forward in the Clinical Assessment for Attention [13], which have been used to assess visuospatial function in patients with posterior cortical atrophy [14], were also administered. Patients with posterior cortical atrophy typically show differences between these span tests, with a markedly short span on the Tapping Span Forward test despite a relatively preserved span on the Digit Span Forward test.…”
Section: Examinationmentioning
confidence: 99%